BIBLIOPHILIC HERITAGE OF EXILE: JUSTINAS K. KARAZIJA - KAUNAS, DOMAS (Knygotyra, 2015)
Bibliophile activity in exile is one of the important and interesting areas of Lithuanian book culture. However, it is not well researched. We rarely talk about valuabel libraries and collections of bibliophiles, except when they are donated to the memory institutions of the homeland. Many of them were collected by physicians, diplomats, artists, and priests who have reached high social standing. Justinas K. Karazija (1892–1991) belonged to the first generation of Lithuanians in the USA. He belonged to the working class (was a steel industry worker) and participated in the social-democratic movement. Karazija’s personal library included publications from 1891–1976 published in exile and in the homeland: books, periodicals, maps. During the later years of his life, the owner has made a bibliographic description of this library and donated it to the American Lithuanian Cultural Archive (ALKA) in Putnam (Connecticut, USA). In this article, six aspects of the library are analysed: the age of publications, languages, publishing places, contents, typology, and the level of individuality. The data allows the author to claim that the library has influenced the formation of the personality, provided possibilities of the intellectual development and stimulated creativity. At the same time it symbolized a minimal, re-located homeland and was oriented to the preservation of the national identity. The library helped to create the physical space and the spiritual microcosm on the basis of the national identity. The case of Karazija’s library proves that this feature of intelectual elevation was characteristic not only to the inteligentsia groups but also to the members of the working social stratas. The microcosm of a personal library enabled them to identify and forecast the future changes of the emigrant community and to define their own place and role in it.
Keywords: ...